#TITLE_ALTERNATIVE# - Hardiman (NIM 250 04 064), Iman
Abstract: Tunneling design before year 1980 usually used empirical method or observational method, and then in practice was accomplished by NATM system. Now the design can be approached more exact by using numerical program of finite element or finite difference. Using those programs calculation can be executed in three dimensional models. The three dimensional model can accommodate developing exact spreading of displacements and stresses in all axis in rock/soil mass. This research used software program based on finite difference method. It compared tunneling excavation between with no and use reinforcements. The reinforcements are rock bolt 1.5 m, shotcrete 10 cm, invert 50 cm (type 1) and rock bolt 1.5 m, shotcrete 20 cm, invert 50 cm (type 2). It means that reinforcement type 2 has more strength than reinforcement type 1. The purpose of this comparison in the research is evaluating the difference of displacements and stresses that might be developed in models. Further can be determined the optimum design of reinforcement for Piyungan - Gading tunnel. The result of this research was found that tunneling excavation at Piyungan-Gading location requires reinforcement. The excavation with no reinforcement produced a large displacement and uncomforted factor of safety. From the comparison of reinforcement was found that the optimum reinforcement for Piyungan-Gading tunnel is rock bolt 1.5 m, shotcrete 10 cm, invert 50 cm (type 1). It was concluded from result of calculation of reinforcement rock bolt 1.5 m, shotcrete 20 cm, invert 50 cm (type 2) does not develop the significant difference with rock bolt 1.5 m, shotcrete 10 cm, invert 50 cm (type 1). The research did not take into account installation of steel ribs-in field usually placed immediately as a temporary support - and fault in rock mass. Steel ribs usually reduce rate of displacement and maintain stress in higher value, but fault has affect contrary.